(3OjhGf HGeNQeIs - (3YeQ Hf YHO Gddg HGeNQeI GdgLQGfj GdTjHGfj GdMVQej,J (B952 (3g` s ((3YHOGddg Hf YhV GdbYjWj s)
(3ChdgG (B:s
(3jG Vfjfj Vfj MGdj hdG CWeY HMjdg MjdI GdYHO ajeG bOQ Gddg bdjdI s
(3BNQgG (B:s
(3hGLYd UdGJc hGdSdGe JMagG CHOkG Ydi NjQ GdCfGe hBdg SQ GdhLhO eMeO hCejQg hefjQg HebGdg haYGdg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B70s
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B213s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B36 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdCOHs